STARTEGI GURU TAHFIZ DALAM MENGEMBANGKAN KELAS TAHFIZ DI MTS AL ITTIHAD BELUNG PONCOKUSUMO MALANG - Khofifatus Su’aidah; Dian Mohammad Hakim; Arief Ardiansyah (VICRATINA, 2022)
Teacher strategy is a way how teachers can achieve the goals that have been determined optimally, both from planning and implementation, because teachers as professional educators and have great responsibility in the learning process. The aims of this study were to: 1) Find out the planning activities for the tahfiz class learning development at MTs Al Ittihad Belung Poncokusumo Malang. 2) Knowing the implementation of tahfiz class learning activities at MTs Al Ittihad Belung Poncokusumo Malang. 3) Knowing the evaluation of learning development activities for the tahfiz class at MTs Al Ittihad Belung Poncokusumo Malang. This study uses descriptive qualitative research methods. For data collection the methods used are: 1) Observation 2) Interview 3) Documentation. Research informants were the principal of MTs Al Ittihad, Tahfiz teachers of MTs Al Ittihad, and Tahfiz students of MTs Al Ittihad. Based on the results of the study, it can be concluded that the strategy consists of several actions, namely: a) giving assignments and memorization targets. b) guiding students to always be muraja'ah. c) graduation for students who have graduated. d) Give certificates to students who meet the target.